2018
DOI: 10.13005/bpj/1467
|View full text |Cite
|
Sign up to set email alerts
|

GC MS Analysis of One Ayurvedic Preparation ‘Aswagandharishtam

Abstract: Aswagandharishtam is classical medicine for diseases pertaining to nervous system and digestive system prepared by a number of plants and plant parts. The present work is to know the types of biomolecules present in it by GC MS analysis. Aswagandharishtam was procured from standard Ayurvedic outlet and was subjected to Gas Chromatography Mass Spectrometry after due processing. The GC MS analysis of Aswagandharishtam has shown some promising molecules like Prostaglandin A2, Cholesterol, Piperine, Gentamicin a, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Additionally, hexadecanoic acid methyl ester [39], 9,12,15-octadecatrienoic acid methyl ester, which was present at the highest level relative to the other constituents [42], and methyl stearate [45] were the identified fatty acids methyl esters that are known to exert antioxidant and anticancer effects. However, the fatty acid methyl ester cis-5,8,11-eicosatrienoic acid methyl ester exerts anti-inflammation-related effects [48]. The identified diterpene was phytol, of which there was a considerable amount relative to the other components, and it has antioxidative stress and anticancer activities [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, hexadecanoic acid methyl ester [39], 9,12,15-octadecatrienoic acid methyl ester, which was present at the highest level relative to the other constituents [42], and methyl stearate [45] were the identified fatty acids methyl esters that are known to exert antioxidant and anticancer effects. However, the fatty acid methyl ester cis-5,8,11-eicosatrienoic acid methyl ester exerts anti-inflammation-related effects [48]. The identified diterpene was phytol, of which there was a considerable amount relative to the other components, and it has antioxidative stress and anticancer activities [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Hemidesmus indicus has numerous medicinal properties varying from chemo-preventive, anti-diarrheal, anti-cancerous, wound healing power, immunomodulatory, antioxidant, anti-venoms, antileprotic, diuretic properties etc. (Kotteswari et al, 2018). Previous studies reported in vitro antibacterial activity of H. indicus n-butanolic extract's inhibitory activity against human pathogenic bacterial strains viz.…”
Section: Discussionmentioning
confidence: 99%
“…Ashwagandha (winter cherry), is an important medicinal herb in Indian Ayurveda, for more than 3000 years used as indigenous medicinal herb (Murthy et al 2010) and cultivated (Kotteswari et al 2018). Indian ginseng is the other name given based on its reported properties like, sedative, tonic, adaptogens, hypnotic, analgesic, diuretic, antipyretic, abortifacient, and anti-in ammatory (Murthy et al 2010).…”
Section: Introductionmentioning
confidence: 99%